Acute lower GI bleeding in the UK: patient characteristics, interventions and outcomes in the first nationwide audit. Issue 4 (1st February 2017) - Oakland, Kathryn; Guy, Richard; Uberoi, Raman; Hogg, Rachel; Mortensen, Neil; Murphy, Michael F; Jairath, Vipul
Abstract : Objective: Lower GI bleeding (LGIB) is a common reason for emergency hospital admission, although there is paucity of data on presentations, interventions and outcomes. In this nationwide UK audit, we describe patient characteristics, interventions including endoscopy, radiology and surgery as well as clinical outcomes. Design: Multicentre audit of adults presenting with LGIB to UK hospitals over 2 months in 2015. Consecutive cases were prospectively enrolled by clinical teams and followed for 28 days. Results: Data on 2528 cases of LGIB were provided by 143 hospitals. Most were elderly (median age 74 years) with major comorbidities, 29.4% taking antiplatelets and 15.9% anticoagulants. Shock was uncommon (58/2528, 2.3%), but 666 (26.3%) received a red cell transfusion. Flexible sigmoidoscopy was the most common investigation (21.5%) but only 2.1% received endoscopic haemostasis. Use of embolisation or surgery was rare, used in 19 (0.8%) and 6 (0.2%) cases, respectively. 48% patients underwent no inpatient investigations. The most common diagnoses were diverticular bleeding (26.4%) and benign anorectal conditions (16.7%). Median length of stay was 3 days, 13.6% patients rebled during admission and 4.4% were readmitted with bleeding within 28 days. In-hospital mortality was 85/2528 (3.4%) and was highest in established inpatients (17.8%, p<0.0001) and in patients experiencing rebleeding (7.1%, p<0.0001). Conclusions: Patients with LGIB have a high burden of comorbidity and frequent antiplatelet or anticoagulant use. Red cell transfusion was common but most patients were not shocked and required no endoscopic, radiological or surgical treatment. Nearly half were not investigated. In-hospital mortality was related to comorbidity, not severe haemorrhage.